Method for determining the silicon side and the carbon side of a silicon carbide wafer
By coating dyne liquid on the silicon carbide wafer and observing the wetting condition of the liquid coating, the problem that the prior art is difficult to distinguish between the silicon surface and the carbon surface of the silicon carbide wafer is solved, and a fast, convenient and lossless distinction effect is achieved.
Patent Information
- Application Number
- CN202211636555.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The prior art is difficult to quickly, conveniently and without loss distinguishing the silicon surface and carbon surface of silicon carbide wafers, especially on cutting sheets and grinding sheets with high surface roughness.
The silicon surface and carbon surface are judged by coating the dyne liquid on the surface of the silicon carbide wafer and the wetting condition of the liquid coating. The liquid coating has continuous and uninterrupted and unshrinkable conditions, which is the silicon surface, and the crystal surface of the liquid droplets is exposed as the carbon surface.
It realizes the rapid, convenient and lossless distinction between the silicon surface and carbon surface of silicon carbide wafers, and is suitable for different types and structures of silicon carbide wafers, including tablets with large surface roughness.
Smart Images

Figure CN116165339B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor materials. Specifically, the present invention relates to a method for determining the silicon surface and the carbon surface of a silicon carbide wafer. Background Art
[0002] Silicon carbide (SiC) is one of the widely-watched wide-bandgap semiconductor materials. It has the advantages of low density, large bandgap (at room temperature, the bandgap of 4H-SiC is 3.2 eV), high breakdown field strength (about 10 times that of Si), high saturated electron mobility (about 2 times that of Si), high thermal conductivity (3 times that of Si, 10 times that of GaAs) and good chemical stability. It is an ideal substrate material for making high-frequency, high-voltage, high-power devices and blue light-emitting diodes. It has important application potential in electric vehicles, rail transit, high-voltage power transmission and transformation, photovoltaics, 5G communications and other fields.
[0003] 4H-SiC and 6H-SiC have hexagonal structures with a space group of P63mc. 15R-SiC has a trigonal structure with a space group of R3m. These three types of silicon carbide crystals are polar crystals with two polar faces: the carbon polar face (usually called the carbon face) and the silicon polar face (usually called the silicon face). When power devices are prepared using SiC as a substrate, epitaxial growth is usually performed on the Si face, while when SiC single crystals are grown using the physical vapor transport (PVT) method, the C face is usually used as the growth face for growth. It can be seen that it is very important to determine the silicon face and carbon face of the SiC wafer.
[0004] At present, a variety of methods have been used to distinguish the silicon side and carbon side of SiC wafers. Commonly used methods include: etching method, atomic force microscopy, Auger electron spectroscopy, X-ray diffraction, etc.
[0005] The silicon side and carbon side of SiC wafer can be distinguished by etching method. The principle is as follows: the silicon and carbon sides of SiC wafer are distinguished by the different reaction ability and reaction rate of the silicon side and carbon side with molten alkali. Since the surface free energy of the silicon side is larger, the etching rate is greater than the etching rate of the carbon side. It is easy to form corrosion pits on the silicon side, but not on the carbon side, and the morphology of the corrosion pits on the silicon side and the carbon side is different. Reference D. Zhuang et al., Wet etching of GaN, AlN, and SiC: areview, Materials Science and Engineering R 48 (2005) 1-46. However, this method will damage the wafer, and the molten alkali used is potentially dangerous to the operator.
[0006] The Chinese patent (CN201310610814.2) uses an atomic force microscope (AFM) to measure the surface roughness of the silicon surface and the carbon surface. The silicon surface and the carbon surface are determined based on the difference in surface roughness. Although this method is a non-destructive analysis and characterization method, it has high requirements on the surface processing quality of SiC wafers, large errors, and low reliability.
[0007] Using an atomic force microscope and the contact mode of AFM, the force-distance curve between the probe tip and the wafer surface is measured, and the desorption force required to pull the probe off the wafer surface is derived. The silicon surface and the carbon surface are judged according to the magnitude of the desorption force, where the desorption force of the silicon surface is greater than that of the carbon surface. References Di Gan et al., Identification of 6H-SiC polar faces with pull-off force of atomic force microscopy, Applied Surface Science 390 (2016) 917-923.
[0008] The polarity of silicon carbide can be determined by bombarding the surface of silicon carbide wafers with low-energy particles based on the ratio of the Auger peaks of carbon and silicon. The carbon surface has a larger ratio of the Auger peaks of carbon and silicon, while the silicon surface has a smaller ratio. References G. Battistig et al., Polarity dependent carbon enrichment on 6H–SiC{0 0 0 1}due to low energy ion bombardment, Surface Science 526 (2003) L133–L136.
[0009] The Chinese patent (CN 114509459 A) distinguishes the silicon side and the carbon side based on the difference in X-ray diffraction intensity between the silicon side and the carbon side of the conductive SiC wafer and the black core unique to the growth of the conductive SiC wafer, but this method requires that the size of the SiC wafer cannot be too large.
[0010] Although the above methods can be used to determine the silicon side and carbon side of a silicon carbide wafer, they are not very convenient to implement, and it is difficult to distinguish the silicon side and carbon side of wafers with greater surface roughness, such as cutting wafers and grinding wafers.
[0011] In view of this, there is an urgent need for a fast, convenient and non-destructive method to determine the silicon surface and carbon surface of SiC substrate wafers, polishing wafers, grinding wafers and cutting wafers. Summary of the invention
[0012] The purpose of the present invention is to provide a method for determining the silicon surface and carbon surface of a silicon carbide wafer. The method is a fast, convenient and non-destructive method for determining the silicon surface and carbon surface of a SiC substrate, polishing, grinding and cutting wafer.
[0013] The above-mentioned object of the present invention is achieved through the following technical solutions.
[0014] The present invention provides a method for determining the silicon surface and the carbon surface of a silicon carbide wafer, comprising the following steps:
[0015] (1) Clean the surface of silicon carbide wafer;
[0016] (2) allowing the dyne liquid to form liquid coatings on two surfaces of the cleaned silicon carbide wafer respectively;
[0017] (3) The silicon surface and the carbon surface are determined based on the following wetting conditions of the dyne liquid on the surface of the silicon carbide wafer: if the liquid coating is continuous and uninterrupted without shrinkage, the surface is a silicon surface; if the liquid coating is intermittent and forms droplets, and part of the crystal surface is exposed, the surface is a carbon surface.
[0018] The inventors of the present application unexpectedly discovered that by applying dyne liquid to the surface of a silicon carbide wafer, the carbon side and the silicon side of the silicon carbide wafer can be accurately identified based on the wetting conditions.
[0019] Preferably, in the method of the present invention, the dyne liquid forms a rectangular liquid coating on both surfaces of the silicon carbide wafer.
[0020] Preferably, in the method of the present invention, the crystal structure type of the silicon carbide wafer in step (1) is 4H, 6H or 15R.
[0021] Preferably, in the method of the present invention, the doping type of the silicon carbide wafer in step (1) is n-type, p-type or semi-insulating type.
[0022] Preferably, in the method of the present invention, the wafer surface of the silicon carbide wafer in step (1) is oriented in the C-axis direction or within 8° from the C-axis direction.
[0023] Preferably, in the method of the present invention, the cleaning of the surface of the silicon carbide wafer in step (1) is performed by a method comprising the following steps:
[0024] First, ultrasonic cleaning is performed with dilute sulfuric acid and alcohol for 2 to 20 minutes respectively, and then ultrasonic cleaning is performed with deionized water for 2 to 20 minutes to remove stains and adsorbed particles on the surface of the chip.
[0025] Preferably, in the method of the present invention, the dyne solution complies with the international standard ISO 8296-2003.
[0026] Preferably, in the method of the present invention, the dyne value of the dyne solution is 36 mN / m to 44 mN / m.
[0027] Preferably, in the method of the present invention, the step of forming the liquid coatings on both surfaces of the silicon carbide wafer with the dyne liquid is performed by coating with a dyne pen.
[0028] Preferably, in the method of the present invention, the dyne pen is a special pen having a fiber pen tip and a pen core filled with dyne liquid that complies with the international standard ISO 8296-2003, and the diameter of the dyne pen tip is 1 to 10 mm.
[0029] Preferably, in the method of the present invention, the dyne liquid is made to form liquid coatings on both surfaces of the silicon carbide wafer respectively by coating with a cotton swab dipped in the dyne liquid.
[0030] Preferably, in the method of the present invention, the cotton swab is made of absorbent cotton or fiber.
[0031] Preferably, in the method of the present invention, the diameter of the cotton swab is 1 to 10 mm.
[0032] Preferably, in the method of the present invention, the wafer processing type of the silicon carbide wafer in step (1) is a cutting wafer, a grinding wafer, a polishing wafer or a substrate wafer.
[0033] Preferably, in the method of the present invention, the cutting blade is a wafer obtained by cutting a silicon carbide ingot through a single-wire saw or a multi-wire saw, and the surface roughness is 0.2 to 2 μm; the grinding blade is a wafer obtained by cutting a silicon carbide blade through a single-sided grinder, a double-sided grinder or a thinning machine, and the surface roughness is 20 to 80 nm; the polishing blade is a wafer obtained by a silicon carbide grinding blade through a mechanical polishing machine, and the surface roughness is 1 to 5 nm; the substrate blade is a wafer obtained by chemical mechanical polishing and cleaning of a silicon carbide polishing blade, and the surface roughness is less than 0.5 nm.
[0034] In a specific embodiment of the present invention, the cleaning of the silicon carbide wafer surface in step (1) is performed by a method comprising the following steps:
[0035] (i) ultrasonically cleaning the wafer with dilute sulfuric acid and alcohol for 10 minutes respectively;
[0036] (ii) ultrasonically cleaning the wafer with deionized water for 10 minutes;
[0037] (iii) Use a hair dryer to dry or allow to evaporate naturally.
[0038] In a specific embodiment of the present invention, the dyne liquid of the present invention complies with the international standard ISO 8296-2003, and is a mixture of formamide, ethylene glycol monoethyl ether, methanol, water and a colorant. The dyne pen is a special pen having a fiber pen head and a pen core filled with dyne liquid that complies with the international standard ISO 8296-2003.
[0039] Compared with the prior art, the present invention has at least the following beneficial effects:
[0040] The present invention provides a method for quickly, conveniently and non-destructively determining the silicon and carbon surfaces of SiC substrates, polishing sheets, grinding sheets and cutting sheets, the essence of which is to use the interface energy anisotropy of silicon carbide to distinguish different crystal planes. Compared with the publicly reported methods, the present method has a wider application range and is applicable to silicon carbide wafers with crystal structure types of 4H, 6H, 15R, and doping types of n-type, p-type or semi-insulating type, and is applicable to silicon carbide wafers with large surface roughness, such as cutting sheets and grinding sheets, which are difficult to determine the silicon-carbon surface by existing methods.
[0041] Compared with the publicly reported methods, the method of the present invention does not cause any damage to the silicon carbide wafer, and the testing process is safe. Compared with all existing non-destructive testing methods (such as using atomic force microscopy and X-ray diffraction), the method of the present invention is simpler and faster, and can distinguish the silicon-carbon surface in just a few seconds, is independent of equipment and environment, and has extremely low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0043] Figure 1 1 is a test result diagram of the silicon surface and the carbon surface of the semi-insulating 4H-SiC substrate obtained in Example 1 of the present invention;
[0044] Figure 2 1 is a test result diagram of the silicon surface and the carbon surface of the n-type 4H-SiC substrate obtained in Example 2 of the present invention;
[0045] Figure 3 1 is a graph showing the test results of the silicon surface and the carbon surface of the p-type 4H-SiC polished wafer obtained in Example 3 of the present invention;
[0046] Figure 4 1 is a graph showing the test results of the silicon surface and the carbon surface of the p-type 6H-SiC polishing sheet obtained in Example 4 of the present invention;
[0047] Figure 5 1 is a graph showing the test results of the silicon side and the carbon side of the n-type 4H-SiC cutting blade obtained in Example 5 of the present invention.
[0048] Figure 61 is a test result diagram of the silicon surface and the carbon surface of the semi-insulating 4H-SiC substrate obtained in Comparative Example 1 of the present invention;
[0049] Figure 7 It is a test result diagram of the silicon surface and carbon surface of the n-type 4H-SiC substrate obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0051] The dyne pens and dyne liquids used in the following examples and comparative examples were purchased from Arcotest, Germany, with models 34# to 48#.
[0052] Example 1
[0053] (1) A semi-insulating 4H-SiC substrate with a known silicon-carbon surface and a surface roughness of 0.3 nm (purchased from Beijing Tianke Heda Semiconductor Co., Ltd.) was first ultrasonically cleaned with dilute sulfuric acid and alcohol for 10 minutes respectively, then ultrasonically cleaned with deionized water for 10 minutes, and dried with a hair dryer;
[0054] (2) Use a dyne pen with a dyne value of 40 mN / m to evenly apply a rectangular shape on both sides of the cleaned semi-insulating 4H-SiC substrate;
[0055] (3) The silicon-carbon surface can be determined based on the wetting condition of the dyne liquid on the chip surface.
[0056] Figure 1 That is the test result diagram of the silicon surface and carbon surface of the semi-insulating 4H-SiC substrate obtained by using Example 1 of the present invention. The liquid coating spreads well on the silicon surface, while on the carbon surface, the wetting degree of the liquid coating is significantly reduced, the dyne liquid in most areas shrinks into droplets, and part of the wafer is exposed. The silicon surface and carbon surface obtained by the method of the present invention are consistent with the silicon surface and carbon surface of the semi-insulating 4H-SiC substrate with a known silicon-carbon surface.
[0057] Example 2
[0058] Example 2 is basically the same as Example 1, except that: the test wafer used is an n-type 4H-SiC substrate (purchased from Beijing Tianke Heda Semiconductor Co., Ltd.) with a surface roughness of 0.4 nm; a 40 mN / m dyne pen is used, and the test results are as follows: Figure 2 The test results show that the liquid coating spreads well on the silicon surface, but does not wet the carbon surface and shrinks into droplets. The silicon surface and carbon surface tested by the method of the present invention are consistent with the silicon surface and carbon surface of the n-type 4H-SiC substrate sheet with known silicon-carbon surface.
[0059] Example 3
[0060] Example 3 is basically the same as Example 1, except that: the test wafer used is a p-type 4H-SiC (developed by the Institute of Physics, Chinese Academy of Sciences) polished wafer with a surface roughness of 3 nm; a cotton swab with a diameter of 5 mm is dipped in a 38 mN / m dyne solution, and the test results are as follows: Figure 3 The test results show that the liquid coating spreads well on the silicon surface, while on the carbon surface, the wetting degree of the liquid coating is significantly reduced, the dyne liquid shrinks and exposes part of the wafer. The silicon surface and carbon surface tested by the method of the present invention are consistent with the silicon surface and carbon surface of the p-type 4H-SiC polishing wafer with known silicon-carbon surface.
[0061] Example 4
[0062] Example 4 is basically the same as Example 1, except that: the test wafer used is a p-type 6H-SiC (developed by the Institute of Physics, Chinese Academy of Sciences) polishing wafer with a surface roughness of 50 nm; a cotton swab with a diameter of 4 mm is dipped in a 40 mN / m dyne solution, and the test results are as follows: Figure 4 The test results show that the liquid coating spreads well on the silicon surface, while on the carbon surface, the wetting degree of the liquid coating is significantly reduced, the dyne liquid in most areas shrinks into droplets, and part of the wafer is exposed. The silicon surface and carbon surface tested by the method of the present invention are consistent with the silicon surface and carbon surface of the p-type 6H-SiC polishing sheet with known silicon-carbon surface.
[0063] Example 5
[0064] Example 5 is basically the same as Example 1, except that: the test wafer used is an n-type 4H-SiC (purchased from Beijing Tianke Heda Semiconductor Co., Ltd.) cut wafer with a surface roughness of 1.5 μm; a fiber pen with a diameter of 4 mm is used to dip into a 42 mN / m dyne solution, and the test results are as follows: Figure 5 The test results show that the liquid coating spreads well on the silicon surface, while on the carbon surface, the wetting degree of the liquid coating is significantly reduced, the dyne liquid shrinks and exposes part of the wafer. The silicon surface and carbon surface tested by the method of the present invention are consistent with the silicon surface and carbon surface of the n-type 4H-SiC cutting blade with a known silicon-carbon surface.
[0065] Comparative Example 1
[0066] Comparative Example 1 is basically the same as Example 1. The test wafer used is a semi-insulating 4H-SiC substrate with a surface roughness of 0.3 nm (purchased from Beijing Tianke Heda Semiconductor Co., Ltd.); the difference is that a 48 mN / m dyne pen is used. The test results are as follows: Figure 6The test results show that the liquid coatings on both the silicon and carbon surfaces shrink to form droplets, with some crystal surfaces exposed, and it is impossible to distinguish between the silicon and carbon surfaces of the semi-insulating 4H-SiC substrate.
[0067] Comparative Example 2
[0068] Comparative Example 2 is basically the same as Comparative Example 1, except that: the test wafer used is an n-type 4H-SiC substrate with a surface roughness of 0.4 nm (purchased from Beijing Tianke Heda Semiconductor Co., Ltd.); a 34 mN / m dyne pen is used, and the test results are as follows: Figure 7 From the test results, it can be seen that the liquid coating on both the silicon and carbon surfaces spreads well without shrinkage, and it is impossible to distinguish between the silicon and carbon surfaces of the n-type 4H-SiC substrate.
[0069] It can be seen that the test method of the present invention can accurately distinguish the silicon surface and carbon surface of different types of silicon carbide wafers, and it is found through experiments that the surface energy of the silicon surface of the semi-insulating 4H-SiC substrate, n-type 4H-SiC substrate, p-type 4H-SiC polishing wafer, p-type 6H-SiC grinding wafer and n-type 4H-SiC cutting wafer is greater than that of the carbon surface. The literature (Journal of Crystal Growth 352 (2012) 177-180) reported that the surface energy of the silicon surface of 4H and 6H silicon carbide calculated by first principles is greater than that of the carbon surface. The surface energy of the silicon surface of 4H-SiC calculated from two non-equivalent lattice sites separating two crystal planes is 76.2 mJ / m 2 and 303.1 mJ / m 2 ; The surface energy of the silicon surface of 6H-SiC calculated from the two crystal planes separated by three non-equivalent lattice sites is 49.7 mJ / m 2 , 54.8 mJ / m 2 and 287.2 mJ / m 2 This is also consistent with the experimental results described in the embodiments of the present invention.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for determining a silicon face and a carbon face of a silicon carbide wafer, comprising the following steps: (1) Clean the surface of silicon carbide wafer; (2) allowing the dyne liquid to form a uniform liquid coating on both surfaces of the cleaned silicon carbide wafer; (3) The silicon surface and the carbon surface are determined based on the following wetting conditions of the dyne liquid on the surface of the silicon carbide wafer: if the liquid coating is continuous and uninterrupted without shrinkage, the surface is a silicon surface; if the liquid coating is intermittent and forms droplets, and part of the crystal surface is exposed, the surface is a carbon surface; The crystal structure type of the silicon carbide wafer in step (1) is 4H, 6H or 15R; The doping type of the silicon carbide wafer in step (1) is n-type, p-type or semi-insulating; The dyne value of the dyne solution is 36 mN / m to 44 mN / m.
2. The method according to claim 1, wherein: The wafer surface orientation of the silicon carbide wafer in the step (1) is in the C-axis direction or deviates from the C-axis direction by less than 8°.
3. The method according to claim 1, wherein: Cleaning the surface of the silicon carbide wafer in step (1) is performed by a method comprising the following steps: First, ultrasonic cleaning is performed with dilute sulfuric acid and alcohol for 2 to 20 minutes respectively, and then ultrasonic cleaning is performed with deionized water for 2 to 20 minutes to remove stains and adsorbed particles on the surface of the chip.
4. The method according to claim 1, wherein: The dyne liquid complies with the international standard ISO 8296-2003.
5. The method according to claim 1, wherein: The dyne liquid is applied to form liquid coatings on both surfaces of the silicon carbide wafer by coating with a dyne pen.
6. The method according to claim 5, wherein: The dyne pen is a special pen with a fiber pen head and a pen core filled with dyne liquid that meets the international standard ISO 8296-2003. The diameter of the dyne pen head is 1-10 mm.
7. The method according to claim 1, wherein: The dyne liquid is formed into liquid coatings on both surfaces of the silicon carbide wafer by applying the dyne liquid with a cotton swab.
8. The method according to claim 7, wherein: The cotton swab is made of absorbent cotton or fiber.
9. The method according to claim 7, wherein: The diameter of the cotton swab is 1 to 10 mm.
10. The method according to claim 1, wherein: The wafer processing type of the silicon carbide wafer in step (1) is a cutting wafer, a grinding wafer, a polishing wafer or a substrate wafer.
11. The method according to claim 10, wherein: The cutting blade is a wafer obtained by cutting a silicon carbide ingot through a single-wire saw or a multi-wire saw, and the surface roughness is 0.2 to 2 μm; The grinding sheet is a wafer obtained by a silicon carbide cutting sheet through a single-sided grinder, a double-sided grinder or a thinning machine, and the surface roughness is 20 to 80 nm; The polishing sheet is a wafer obtained by mechanical polishing of a silicon carbide grinding sheet, and the surface roughness is 1 to 5 nm; The substrate sheet is a silicon carbide polishing sheet that has been chemically mechanically polished and cleaned, and the surface roughness is less than 0.5nm.
Citation Information
Patent Citations
Method for distinguishing Si surface from C surface of SiC (silicon carbide) wafer
CN103630708A
Method for distinguishing silicon surface and carbon surface of conductive silicon carbide wafer
CN114509459A
Method for cleaning pollutants on surface of silicon carbide wafer
CN101979160A
Method for identifying single crystal polar surface by utilizing wettability difference
CN111627827A